Etnoastronomia, interculturalidade e formação docente nos planetários do espaço do conhecimento UFMG e do Parque Explora - Leonardo Marques Soares (2017)
Given the need to ensure the right of citizens to basic education, it is essential to rethink the modeling school, curriculum and teacher training, in order to respect the cultural characteristics of different peoples and at the same time, put them in touch with knowledge produced in academia. We analyze teacher training activities in the Knowledge Center UFMG, in Belo Horizonte, and Explora Park in Medellin, where the planetary are used to address knowledge produced in the field of ethnoastronomy related to Guarani and Tayrona ethnicities. We consider that planetary environments are conducive to develop teacher training activities based on the concept of interculturality, stimulating ownership of ethnoastronomy field of knowledge, and characterized by elements that make up the structure of the activity. The central hypothesis is that teachers can appropriate ethnoastronomy field of knowledge through sessions and activities on indigenous astronomy developed in Planetariums in Belo Horizonte and in Medellín. Faced with this situation, the central research question is: how teachers appropriating knowledge of ethnoastronomy in teacher training activities in the planetary UFMG Knowledge Center and Parque Explora? The participants in this study are teachers who attended a short course offered in these institutions and / or scheduled the session "Indigenous Astronomy" for their students. Group discussions were held, questionnaires and interviews with these teachers. The methodology used was content analysis according to Bardin (1977), supported the theoretical framework of Activity Theory (ENGESTRÖM, 1999) and the concept of interculturality (WALSH, 2009). The codes created from the Activity Theory and the concept of interculturality were effective to analyze the ways in which the teaching session appropriated "Indigenous Astronomy" and knowledge of ethnoastronomy. In total 289 were identified appropriations by subjects, reviews by context and by area of activity. It was evident the appropriation of the session by the teachers, in order to stimulate reflection on the knowledge from different points of view and approaches to intercultural pedagogical practices. Were identified different types of tensions related to the practice of interculturality, highlighting some convergences and divergences between education in Brazil and Colombia.